Peranan Al-Qur'an dalam Menyikapi Praktik Pernikahan Sirri: Analisis Tafsir Al-Qur'an terhadap Keabsahan Pernikahan Sirri - Aprianti, Sheila; Galib, Muhammad; Abubakar, Achmad (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
Sirri marriages are marriages not officially registered marriages with state institutions, conducted secretly, or otherwise not made public. The practice has drawn past controversy in Islamic law and state law, particularly with regard to protection rights for women and children. In the eyes of Islamic law, this marriage is legitimate if it fulfills the conditions and pillars as established in the presence of a guardian (wali), two witnesses, and the submission of the marriage contract (ijab and qabul). The fact of an unregistered marriage implies potential legal and social problems associated with its consonance with the values of justice and transparency according to the Qur'an. This research intends to study the Qur'an's role in addressing the occurrence of unregistered marriages, particularly covering verses focusing on the importance of documentation, testimony, and openness in marriage affairs. A hermeneutical approach will help unravel the meanings of Qur'anic verses such as QS. Al-Baqarah [2]: 282 and QS. An-Nisa' [4]: 1 in attempts to establish a more holistic legal interpretation of the findings, suggesting that unregistered marriages qualify as legitimate in religious terms if they meet the pillars and conditions; however, this practice is contradictory to the major principles of transparency and justice and the protection of rights that the Qur'an teaches. Hence, it recommends the requirement of registration as one of these forms of *maṣlahah mursalah* and, thus, a public benefit to prevent social unrest and maintain rights of all concerned parties. This will thus provide a considerable found basis for addressing unregistered marriages from the purview of the Qur'an concerning whether or not they can be religiously valid and legally certain.